Preference and performance of Phyllocnistis citrella Stainton (Lepidoptera:Gracillariidae) on three citrus hosts: Laboratory and field assessment - Goane, Lucía (2008)
The relationship between preference and performance is crucial to the ecology and evolution of plant-insect interactions. Oviposition preference and offspring performance were evaluated for a citrus pest, the leafminer Phyllocnistis citrella (Lepidoptera: Gracillariidae), on three of its host plants: lemon (Citrus limon L. Burm.), orange (Citrus sinensis L. Osbeck), and grapefruit (Citrus paradisi Macfadyen) in Tucumán province (northwest Argentina). Choice and no-choice tests were performed in open and enclosed environments, and performance parameters (development time, survival, pupal size, and sex ratio) were estimated from laboratory rearing and 3-yr field sampling data. Parasitism rates were studied in laboratory choice test and field assessments. Preference trends were inconsistent, with lemon receiving more eggs in some tests, whereas no preference was observed in others. Patterns of host use in the field did not show significant differences among species. Leafminer performance, including parasitism and predation rates, was generally homogeneous among host plants. From these results, lemon, orange, and grapefruit seem to represent intrinsically similar resources for P. citrella populations in northwest Argentina, a trend that was accompanied by a lack of consistent oviposition preferences in foraging females. Ecological conditions might be more important than physiological adaptation in shaping a probably labile host ranking in this pest species.